Enhancing Purchase Intention through Service Quality: The Mediating Role of Customer Satisfaction and Competitive Advantage in Batam City Supermarkets - Budiman, Johny; Maridza, Fidella Dita (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to examine the influence of service quality on customer satisfaction, competitive advantage, and purchase intention among customers of five supermarkets in Batam City: Top 100, DC Supermarket, Hypermart, JC Supermarket, and SNL Food. A quantitative method was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on data collected from 306 respondents. The result indicates that service quality has a significant positive impact on customer satisfaction, competitive advantage, and purchase intention. Furthermore, competitive advantage significantly mediates the relationship between service quality and purchase intention, while customer satisfaction does not show a direct or mediating effect. These findings highlight the strategic importance of service quality in fostering sustainable competitive advantage, which has a stronger influence on consumers’ purchasing decisions than short-term satisfaction. Theoretically, this study contributes to the retail marketing literature. Practically, it provides valuable insights for retail managers to develop service strategies focused on long-term value creation and differentiation.